Psykhe (Santiago) 2014
DOI: 10.7764/psykhe.23.2.562
|View full text |Cite
|
Sign up to set email alerts
|

“No Dejes tus Valores en Casa”: Un Estudio Sobre los Valores de Adultos Emergentes Italianos y sus Padres

Abstract: The aims of this work, involving a convenience sample of 184 emerging adults and both their parents, recruited in universities and worker cooperatives and factories located in northern Italy, were to: (a) compare the emerging adults' and their parents' values to uncover gender and generational specificities, (b) measure value similarities between each emerging adult and his/her parents and between the two parents, and (c) examine the importance of family relationship quality as accounting for value similaritie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 34 publications
0
12
1
1
Order By: Relevance
“…Consistently with the second hypothesis (H2) and with previous studies on basic values ( Barni et al, 2011 ), young athletes were willing to accept these parental values from a moderate to a high degree. Interestingly, adolescents’ level of sport value acceptance seemed to be definitively higher than that showed by previous studies concerning basic values ( Alfieri, Barni, Rosnati, & Marta, 2014 ; Barni et al, 2011 ; Barni, Ranieri, & Scabini, 2012 ). It is likely that sport is a powerful means through which parents can communicate their value messages to their offspring, as their sportive activity may be a topic children are particularly interested in discussing.…”
Section: Discussioncontrasting
confidence: 79%
“…Consistently with the second hypothesis (H2) and with previous studies on basic values ( Barni et al, 2011 ), young athletes were willing to accept these parental values from a moderate to a high degree. Interestingly, adolescents’ level of sport value acceptance seemed to be definitively higher than that showed by previous studies concerning basic values ( Alfieri, Barni, Rosnati, & Marta, 2014 ; Barni et al, 2011 ; Barni, Ranieri, & Scabini, 2012 ). It is likely that sport is a powerful means through which parents can communicate their value messages to their offspring, as their sportive activity may be a topic children are particularly interested in discussing.…”
Section: Discussioncontrasting
confidence: 79%
“…Specifically, Flanagan ( 2003 ) and Flanagan et al ( 2007 ) introduced values with respect to civic attitudes: They defined engagement values to explain the position taken and the relative importance attributed by people to issues of a social or political nature. In their view, a constitutive element of civic values is the experience of group membership together with the experience of socialization in one's family and community in general (Sherrod et al, 2002 ; Marta et al, 2010 ; Marzana et al, 2012 ; Alfieri et al, 2014 ). Wolf ( 2007 ) conducted a meta-analysis of civic values and found that civic values are, in order of the most widely studied to the least: political tolerance, understood as the desire to extend civil rights to all, even to groups we do not like; volunteerism, understood as the contribution of one's time to support the activities of community organizations; political knowledge, understood as the awareness of the political system, current events, and political leaders; social capital, as the extent to which a person is networked within their community; civic skills, understood as the experience in and familiarity with activities used to influence the political process; and patriotism, understood as a visceral positive connection to one's country and respect for its national symbols and rituals.…”
Section: The Literaturementioning
confidence: 99%
“…Implicit family socialization occurs via family interactions and relationships (e.g., family communication, relationship quality, and parenting style). Implicit socialization is more about the transfer of the regulating mechanisms undergirding financial decision-making such as values, attitudes, and beliefs (Alfieri, Barni, Rosnati, & Marta, 2014). It is more about the "why" and "how" of financial management.…”
Section: Family Financial Socialization and Parental Role Modeling Asmentioning
confidence: 99%